Complexity made simple: The value of brief vignettes as a pedagogical tool in public affairs education. Issue 2 (July 2018) - Straussman, Jeffrey D
Introducing a new concept, skill or method to public affairs students always involves a decision about the most effective pedagogical approach that will achieve the instructor's objectives. In public affairs, education concepts are often abstract, complex and contested. One of the approaches that can be effective in introducing public affairs concepts is playfulness—simple anecdotes, mini, one page composite cases and scenarios and even "tricks" that can all be used to motivate a given subject. One technique is to introduce concepts with brief vignettes that have just enough detail to allow students to practice the concepts and apply skills that cut across the management and policy curriculum. Vignettes offer the immediate advantage of quick reflection and decision which can then be followed with deeper investigation and analysis. Students can practice thinking fast and thinking smart. Examples of policy and policy implementation from the author's teaching repertoire are used to illustrate the argument.